Children and family in late antique Egyptian monasticism - Schroeder, Caroline T. (Cambridge University Press, 2021)
"In the 300s, Christians in Egypt and all over the Roman Empire came to the Nile Valley and outlying deserts to become monks, men as well as women. The rhetoric of this movement emphasized a retreat into the wilderness, a retreat away from the city, family, and property - everything one had. Perhaps the most famous passage in monastic hagiography evokes this renunciation of family. Athanasius, author of the Life of Antony, declared that so many people had come to Egypt to become monks that the desert had transformed into a well-populated community:"--